Stress and interpersonal relationships in nursing work on the example of the study group - Zdziebło, Kazimiera; Stępień, Renata; Siudak, Marzanna (Nursing in the 21st Century, 2015)
STRESS AND INTERPERSONAL RELATIONSHIPS IN NURSING WORK ON THE EXAMPLE OF THE STUDY GROUPIntroduction. The working environment is full of stressful conditions that mainly concern the medical profession. In particular, the work of nurses is associated with high levels of occupational stress since they are responsible for helping, contacting the weak, sick or people that simply await medical assistance.Aim. The aim of this study was to assess nurses’ exposure to stress at work.Material and Methodology. The study involved a group of 108 nurses working in different entities of therapeutic activity in Sandomierz. The authors used the diagnostic survey method and a digital questionnaire of their own making. For statistical analysis, they used ANOVA Kruskal-Wallis test for multiple comparisons and medium-rank test for indicators of structure.Results. As many as 82.72% of the surveyed nurses considered their work as stressful. The nurses mention the following factors as the most stressful ones: huge responsibility, low wages, exposure to harmful agents and dying people. The test results (p